Relative age effects in international age group championships: A study of Spanish track and field athletes - Brazo-Sayavera, J.; Martinez-Valencia, M. A.; Müller, L.; Andronikos, G.; Martindale, R. J. J. (PLOS ONE, 2018)
The relative age effect is a well-researched phenomenon, however there is still a dearth of understanding in track and field and female sport. This study investigated the role of relative age on selection for international competition of Spanish age group athletes between 2006-2014. Six hundred and forty two athletes competed for Spain at U20 or U18 age group international competition (n = 359 males; 283 females) across 9 years. The birthdates of these athletes were compared against the population of registered athletes at that time (14,502 males; 10,096 females). The results highlighted the influential role of relative age on selection to these opportunities. In line with previous research, this effect was mediated by age and gender, with stronger effects for both males and younger athletes (U18). The data best supported the `maturation-selection` hypothesis as a mechanism for RAEs. These results highlight the need to carefully consider the role and need for international competitive opportunities at different age groups. A number of possible context relevant solutions are discussed, including correction adjustments techniques and competition structure within track and field.